2021
DOI: 10.3390/s21051772
|View full text |Cite
|
Sign up to set email alerts
|

Visual Features Assisted Robot Localization in Symmetrical Environment Using Laser SLAM

Abstract: Localization for estimating the position and orientation of a robot in an asymmetrical environment has been solved by using various 2D laser rangefinder simultaneous localization and mapping (SLAM) approaches. Laser-based SLAM generates an occupancy grid map, then the most popular Monte Carlo Localization (MCL) method spreads particles on the map and calculates the position of the robot by a probabilistic algorithm. However, this can be difficult, especially in symmetrical environments, because landmarks or fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…However, the mobile robot still cannot localize correctly even if there had a highly accurate map. This situation always appears in symmetrical or similar environments [37], because there are many possible positions where the mobile robot may locate. Without the help of other sensor information, the robot cannot distinguish itself at the door of room 214 or room 215 using data from the laser sensor.…”
Section: Mapping In a Simulated Environmentmentioning
confidence: 99%
“…However, the mobile robot still cannot localize correctly even if there had a highly accurate map. This situation always appears in symmetrical or similar environments [37], because there are many possible positions where the mobile robot may locate. Without the help of other sensor information, the robot cannot distinguish itself at the door of room 214 or room 215 using data from the laser sensor.…”
Section: Mapping In a Simulated Environmentmentioning
confidence: 99%
“…The test results showed that the positioning accuracy of the system was improved. Literature (Ge et al , 2021) proposes an intensity difference weighting method for LOAM feature point matching. In fact, in an environment with obvious structural features, the accuracy requirements can be satisfied by relying only on the geometric information of the point cloud, without consuming more computing resources to add the intensity information of the point cloud.…”
Section: Introductionmentioning
confidence: 99%
“…In early SLAM implementations, range-bearing sensors were usually used for visual robot navigation. With the development of computer vision, the problem of loop closure detection has been taken as image based visual appearance alignment problem, in which image is captured by the robot cameras [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers employ the idea of bag-of-words model (BoW) to SLAM [1,4,5,[7][8][9][10][11][12]. Due to its flexibility, simplicity, BoW has become very popular in visual-related tasks.…”
Section: Introductionmentioning
confidence: 99%